Comparative fiber property and transcriptome analyses reveal key genes potentially related to high fiber strength in cotton (Gossypium hirsutum L.) line MD52ne. Issue 1 (December 2016) - Islam, Md; Fang, David; Thyssen, Gregory; Delhom, Chris; Liu, Yongliang; Kim, Hee
Abstract Background Individual fiber strength is an important quality attribute that greatly influences the strength of the yarn spun from cotton fibers. Fiber strength is usually measured from bundles of fibers due to the difficulty of reliably measuring strength from individual cotton fibers. However, bundle fiber strength (BFS) is not always correlated with yarn strength since it is affected by multiple fiber properties involved in fiber-to-fiber interactions within a bundle in addition to the individual fiber strength. Molecular mechanisms responsible for regulating individual fiber strength remain unknown.Gossypium hirsutum near isogenic lines (NILs), MD52ne and MD90ne showing variations in BFS provide an opportunity for dissecting the regulatory mechanisms involved in individual fiber strength. Results Comprehensive fiber property analyses of the NILs revealed that the superior bundle strength of MD52ne fibers resulted from high individual fiber strength with minor contributions from greater fiber length. Comparative transcriptome analyses of the NILs showed that the superior bundle strength of MD52ne fibers was potentially related to two signaling pathways: one is ethylene and the interconnected phytohormonal pathways that are involved in cotton fiber elongation, and the other is receptor-like kinases (RLKs) signaling pathways that are involved in maintaining cell wall integrity. MultipleRLK s were differentially expressed in MD52ne fibers and localized in genomic regions encompassing the strength quantitative trait loci (QTLs). Several candidate genes involved in crystalline cellulose assembly were also up-regulated in MD52ne fibers while the secondary cell wall was produced. Conclusion Comparative phenotypic and transcriptomic analyses revealed differential expressions of the genes involved in crystalline cellulose assembly, ethylene and RLK signaling pathways between the MD52ne and MD90ne developing fibers. Ethylene and its phytohormonal network might promote the elongation of MD52ne fibers and indirectly contribute to the bundle strength by potentially improving fiber-to-fiber interactions. RLKs that were suggested to mediate a coordination of cell elongation and SCW biosynthesis in other plants might be candidate genes for regulating cotton fiber cell wall assembly and strength.